High-performance composite board prepared from waste wind power blade and preparation method of high-performance composite board

By preparing high-performance composite sheets, using the combination of waste wind power blade powder and degraded glass fiber and thermoplastic resin, the problem of glass fibers that can no longer be used in retired wind power blades is solved, and resource utilization and performance improvement are achieved.

CN119613858AActive Publication Date: 2025-03-14LIAONING LONGYUAN NEW ENERGY DEV CO LTD

Patent Information

Application Number
CN202411637871.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-03-14
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

In the prior art, glass fibers of retired wind power blades cannot be reused, and the boards made of waste wind power blade powder have poor market competitiveness.

Method used

By preparing high-performance composite boards, the material composition includes waste wind power blade powder, waste wind power blade degradation glass fiber, silane coupling agent, thermoplastic resin, compatibility agent, wood powder, filler, lubricant, mold release agent and pigment, and is processed using high-speed mixer, granulator and conical twin-screw extruder and other equipment.

Benefits of technology

The resource utilization of waste wind power blades has been realized, the manufacturing cost of composite panels has been reduced, the tensile, bending and compression resistance of the panels has been improved, and the market competitiveness has been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to a high-performance composite board prepared from waste wind power blades and a preparation method of the high-performance composite board. The high-performance composite board contains a large amount of waste wind power blade powder and waste wind power blade degraded glass fibers, so that the manufacturing cost of the high-performance composite board can be reduced; in addition, powder made of waste wind power blades and regenerated glass fibers obtained through a chemical degradation method can be recycled, resource utilization of the retired wind power blades is achieved, and the resource utilization problem of the retired wind power blades is effectively solved. Besides, the coupling effect of the waste wind power blade powder and the waste wind power blade degraded glass fiber with the thermoplastic resin is good, and under the synergistic effect of the compatilizer, the wood flour, the filler, the lubricant and other materials, the mixing and stirring effect can be improved, and the service life of the material is prolonged. Waste wind power blade powder and waste wind power blade degraded glass fibers can be uniformly dispersed in the high-performance composite board, and the physical properties of tensile resistance, bending resistance and compression resistance of the composite board can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of solid waste treatment, and in particular, to a high-performance composite plate prepared using waste wind turbine blades and a preparation method thereof. Background Art

[0002] Wind turbine blades are one of the core components of wind turbine generators. Currently, most wind turbine blades in service are made of fiber-reinforced thermosetting resin-based composite materials, which have many advantages such as high specific strength, high fatigue resistance, good corrosion resistance and weather resistance. Their service life is generally 20-25 years. The chemical properties of wind turbine blades are extremely stable and can last for decades or even hundreds of years without rotting. As time goes by, early installed wind turbines will be retired one after another, which will produce a large number of retired wind turbine blades.

[0003] At present, a considerable number of scientific research institutions and enterprises have conducted relevant research on the resource utilization of retired wind turbine blades. The mainstream treatment methods on the market are physical disposal and chemical degradation. Among them, the physical disposal method cuts and crushes the waste wind turbine blades and uses them as fillers to make some wood-plastic recycled boards, but their performance is only equal to or slightly weaker than traditional wood-plastic materials, and their market competitiveness is poor; the chemical degradation method has a relatively high cost, and the recycled glass fiber cannot be used again to manufacture blades, and its downstream destination has yet to be developed. Summary of the invention

[0004] The purpose of the present invention is to provide a high-performance composite board made from waste wind turbine blades and a preparation method thereof, so as to solve the problems in the prior art that the glass fiber obtained by degradation cannot be reused and the boards made from waste wind turbine blade powder have poor market competitiveness.

[0005] In order to achieve the above-mentioned object, the first aspect of the present disclosure provides a high-performance composite board prepared by using waste wind turbine blades, wherein the materials for preparing the high-performance composite board include waste wind turbine blade materials, silane coupling agents, thermoplastic resins, compatibilizers, wood powder, fillers, lubricants, release agents and pigments; wherein the waste wind turbine blade materials include waste wind turbine blade powder and waste wind turbine blade degraded glass fibers; Relative to 160 parts by weight of the thermoplastic resin, the content of the waste wind turbine blade powder is 50-200 parts by weight, the content of the degraded glass fiber of the waste wind turbine blade is 5-40 parts by weight, the content of the silane coupling agent is 5-50 parts by weight, the content of the compatibilizer is 5-80 parts by weight, the content of the wood powder is 50-200 parts by weight, the content of the filler is 5-50 parts by weight, the content of the lubricant is 5-35 parts by weight, the content of the release agent is 5-35 parts by weight, and the content of the pigment is 1-10 parts by weight.

[0006] Optionally, the silane coupling agent includes KH550 and / or KH560.

[0007] Optionally, the particle size of the waste wind turbine blade powder is 40-200 mesh; the length of the degraded glass fiber of the waste wind turbine blade is 0.5-3 cm.

[0008] Optionally, relative to 160 parts by weight of the thermoplastic resin, the content of the waste wind turbine blade powder is 100-180 parts by weight, the content of the degraded glass fiber of the waste wind turbine blade is 10-30 parts by weight, the content of the silane coupling agent is 10-45 parts by weight, the content of the compatibilizer is 10-70 parts by weight, the content of the wood powder is 100-180 parts by weight, the content of the filler is 10-40 parts by weight, the content of the lubricant is 10-30 parts by weight, the content of the release agent is 10-30 parts by weight, and the content of the pigment is 2-8 parts by weight.

[0009] Optionally, the thermoplastic resin includes polypropylene and / or polyethylene; the wood powder includes poplar powder and / or eucalyptus powder; the particle size of the wood powder is 50-150 mesh; the compatibilizer includes maleic anhydride grafted polypropylene and / or maleic anhydride grafted polyethylene; the filler includes calcium carbonate and / or talc; the lubricant includes polyethylene wax; the release agent includes one or more of sodium stearate, magnesium stearate and calcium stearate; the pigment includes red iron oxide and / or yellow iron oxide.

[0010] A second aspect of the present disclosure provides a method for preparing the high-performance composite board according to the first aspect, the method comprising: S1. Putting waste wind turbine blade materials and silane coupling agent dilution liquid into a high-speed mixer for premixing; the waste wind turbine blade materials include waste wind turbine blade powder and waste wind turbine blade degraded glass fiber; S2, putting the thermoplastic resin, compatibilizer, wood powder, filler, lubricant, release agent and pigment into the high-speed mixer and mixing with the mixed material in step S1 to obtain a composite board mixture; S3, allowing the composite plate mixture to enter a granulator for granulation treatment to obtain composite resin particles; S4, allowing the composite resin particles to enter a conical twin-screw extruder for extrusion molding to obtain a high-performance composite sheet; The material composition of the composite board mixture includes: relative to 160 parts by weight of the thermoplastic resin, the content of the waste wind turbine blade powder is 50-200 parts by weight, the content of the degraded glass fiber of the waste wind turbine blade is 5-40 parts by weight, the content of the silane coupling agent is 5-50 parts by weight, the content of the compatibilizer is 5-80 parts by weight, the content of the wood powder is 50-200 parts by weight, the content of the filler is 5-50 parts by weight, the content of the lubricant is 5-35 parts by weight, the content of the release agent is 5-35 parts by weight, and the content of the pigment is 1-10 parts by weight.

[0011] Optionally, step S1 includes: S11, cutting, crushing and sieving the waste wind turbine blades in sequence to obtain the waste wind turbine blade powder with a particle size of 40-200 mesh; S12, cutting, chemically degrading, washing, drying and segmenting the waste wind turbine blades in sequence to obtain the degraded glass fibers of the waste wind turbine blades with a length of 0.5-3 cm; S13, placing the waste wind turbine blade powder and the waste wind turbine blade degraded glass fiber into the high-speed mixer for stirring, and spraying the silane coupling agent dilution liquid into the mixer during the stirring process; S14, continue stirring the high-speed mixer at a rotation speed of 550-650 r / min for 10-30 min; S15, cooling the mixture obtained in step S14 to 20-30°C.

[0012] Optionally, the mass concentration of the silane coupling agent in the silane coupling agent dilution solution is 30-60%.

[0013] Optionally, step S3 also includes that the conditions of the granulation treatment include: the temperature of the feeding section in the granulator is 160-210°C, the temperature of the plasticizing section in the granulator is 150-190°C, and the temperature of the extrusion section in the granulator is 140-180°C.

[0014] Optionally, step S4 also includes that the extrusion molding conditions include: the temperature of the feeding section in the conical twin-screw extruder is 170-220°C, the temperature of the plasticizing section in the conical twin-screw extruder is 150-200°C, and the temperature of the extrusion section in the conical twin-screw extruder is 140-180°C.

[0015] Through the above technical scheme, the high-performance composite board prepared by the present invention contains a large amount of waste wind turbine blade powder and waste wind turbine blade degraded glass fiber, which can not only reduce the manufacturing cost of the high-performance composite board, but also can recycle and reuse the powder made of waste wind turbine blades and the regenerated glass fiber obtained by chemical degradation, so as to realize the resource utilization of retired wind turbine blades and effectively solve the problem of resource utilization of retired wind turbine blades. In addition, the coupling effect of waste wind turbine blade powder and waste wind turbine blade degraded glass fiber with thermoplastic resin is good, and under the synergistic effect of materials such as compatibilizers, wood powder, fillers and lubricants, the mixing and stirring effect can be improved, and the waste wind turbine blade powder and waste wind turbine blade degraded glass fiber can be evenly dispersed in the high-performance composite board, which can improve the tensile, bending and compression resistance of the composite board.

[0016] Other features and advantages of the present disclosure will be described in detail in the following detailed description. DETAILED DESCRIPTION

[0017] The specific embodiments of the present disclosure are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present disclosure, and are not used to limit the present disclosure.

[0018] The first aspect of the present disclosure provides a high-performance composite board prepared using waste wind turbine blades, wherein the materials for preparing the high-performance composite board include waste wind turbine blade materials, silane coupling agents, thermoplastic resins, compatibilizers, wood flour, fillers, lubricants, release agents and pigments; wherein the waste wind turbine blade materials include waste wind turbine blade powder and waste wind turbine blade degraded glass fiber; relative to 160 parts by weight of the thermoplastic resin, the content of the waste wind turbine blade powder is 50-200 parts by weight, the content of the waste wind turbine blade degraded glass fiber is 5-40 parts by weight, the content of the silane coupling agent is 5-50 parts by weight, the content of the compatibilizer is 5-80 parts by weight, the content of the wood flour is 50-200 parts by weight, the content of the filler is 5-50 parts by weight, the content of the lubricant is 5-35 parts by weight, the content of the release agent is 5-35 parts by weight, and the content of the pigment is 1-10 parts by weight.

[0019] Through the above technical scheme, the high-performance composite board prepared by the present invention contains a large amount of waste wind turbine blade powder and waste wind turbine blade degraded glass fiber, which can not only reduce the manufacturing cost of the high-performance composite board, but also can recycle and reuse the powder made of waste wind turbine blades and the regenerated glass fiber obtained by chemical degradation, so as to achieve the purpose of resource utilization of retired wind turbine blades. In addition, the coupling effect of waste wind turbine blade powder and waste wind turbine blade degraded glass fiber with thermoplastic resin is good, and under the synergistic effect of materials such as compatibilizers, wood powder, fillers and lubricants, the mixing and stirring effect can be improved, and the waste wind turbine blade powder and waste wind turbine blade degraded glass fiber can be evenly dispersed in the high-performance composite board, which can improve the composite board's physical properties of tensile resistance, bending resistance and compression resistance.

[0020] In a preferred embodiment, relative to 160 parts by weight of the thermoplastic resin, the content of the waste wind turbine blade powder is 100-180 parts by weight, the content of the degraded glass fiber of the waste wind turbine blade is 10-30 parts by weight, the content of the silane coupling agent is 10-45 parts by weight, the content of the compatibilizer is 10-70 parts by weight, the content of the wood powder is 100-180 parts by weight, the content of the filler is 10-40 parts by weight, the content of the lubricant is 10-30 parts by weight, the content of the release agent is 10-30 parts by weight, and the content of the pigment is 2-8 parts by weight.

[0021] In a further preferred embodiment, relative to 160 parts by weight of the thermoplastic resin, the content of the waste wind turbine blade powder is 150-170 parts by weight, the content of the degraded glass fiber of the waste wind turbine blade is 15-25 parts by weight, the content of the silane coupling agent is 20-40 parts by weight, the content of the compatibilizer is 20-60 parts by weight, the content of the wood powder is 150-170 parts by weight, the content of the filler is 20-30 parts by weight, the content of the lubricant is 15-25 parts by weight, the content of the release agent is 15-25 parts by weight, and the content of the pigment is 3-6 parts by weight.

[0022] In one embodiment, by reasonably proportioning the components in the raw materials of the high-performance composite board, the mechanical properties of the high-performance composite board can be further enhanced. Specifically, the tensile strength of the composite board is above 20.5 MPa, the bending strength is above 48 MPa, and the compressive strength is above 52 MPa.

[0023] In one embodiment, the particle size of the waste wind turbine blade powder is 40-200 mesh.

[0024] In a preferred embodiment, the particle size of the waste wind turbine blade powder is 50-100 mesh.

[0025] In this embodiment, the waste wind turbine blade powder refers to waste wind turbine blades that are cut, crushed and sieved in sequence. Using waste wind turbine blade powder of appropriate particle size can improve the uniformity of each component during the mixing process, thereby improving the high-performance composite board with strong tensile strength, bending strength and compressive strength.

[0026] In one embodiment, the length of the degraded glass fiber from waste wind turbine blades is 0.5-3 cm.

[0027] In a preferred embodiment, the length of the degraded glass fiber from waste wind turbine blades is 1-2 cm.

[0028] In this embodiment, the waste wind turbine blade degraded glass fiber refers to waste wind turbine blades that are cut, chemically degraded, washed, dried and cut into segments. The use of waste wind turbine blade degraded glass fiber of appropriate length to prepare high-performance composite sheets can provide better tensile force when stretched, bent and compressed, and thus can make the high-performance composite sheets have stronger tensile strength, bending strength and compressive strength.

[0029] In one embodiment, the silane coupling agent disclosed in the present invention is a conventional choice in the art, and this application does not make any special requirements. For example, the silane coupling agent includes silane coupling agent KH550 and / or silane coupling agent KH560.

[0030] In this embodiment, by adding a silane coupling agent to the raw materials, the non-hydrolyzable organic functional group at one end of the silane coupling agent can be combined with the thermoplastic resin, and the hydrolyzable group at the other end of the silane coupling agent can be combined with the glass fiber exposed on the surface of the waste wind turbine blade powder and the degraded glass fiber of the waste wind turbine blade, thereby improving the graft coupling effect between the waste wind turbine blade material and the thermoplastic resin, thereby improving the mechanical properties of the high-performance composite board. Vinyl silane coupling agents and methacryloxy silane coupling agents can further improve the bonding strength between such silane coupling agents and polyester resins or acrylic resins; epoxy silane coupling agents can improve the bonding strength between such silane coupling agents and epoxy resins.

[0031] In one embodiment, the thermoplastic resin used in the present disclosure is conventionally selected in the art and is not specifically required in the present application. For example, the thermoplastic resin includes polyethylene and / or polypropylene.

[0032] In one embodiment, the wood powder includes poplar wood powder and / or eucalyptus wood powder.

[0033] In one embodiment, the particle size of the wood powder is 50-150 mesh.

[0034] In a preferred embodiment, the particle size of the wood powder is 60-100 mesh.

[0035] In this embodiment, wood powder is used in the high-performance composite board disclosed in the present invention. On the one hand, the wood powder can act as a filler in the entire board. During the hot stirring process with the thermoplastic resin, the wood powder can be fully dispersed therein to obtain a board with higher hardness. On the other hand, the wood powder can be made from chips or scraps during wood processing, which can further reduce the production cost of the board.

[0036] In one embodiment, in order to further improve the mechanical properties of the high-performance composite board, a filler may be used in the high-performance composite board. The filler disclosed in the present invention includes calcium carbonate and / or talcum powder.

[0037] In one embodiment, the compatibilizer used in the present disclosure includes maleic anhydride grafted polypropylene and / or maleic anhydride grafted polyethylene.

[0038] In this embodiment, maleic anhydride grafted polypropylene and maleic anhydride grafted polyethylene are formed by introducing strongly polar side groups on the non-polar molecular main chain, and maleic anhydride grafted polypropylene or polyethylene can become a bridge to enhance the adhesion and compatibility between polar materials and non-polar materials. Adding maleic anhydride grafted polypropylene when wood powder and filler are filled with polypropylene can greatly improve the affinity between filler and polypropylene and the dispersion of filler, thus effectively enhancing the dispersion of filler in polypropylene, thereby improving the tensile and impact strength of filled polypropylene.

[0039] In one embodiment, the lubricant includes one or more of polyethylene wax, stearic acid, methyl stearate and capric amide, preferably polyethylene wax.

[0040] In this embodiment, by adding lubricants to the high-performance composite sheet material, not only can the softness and tensile properties of the material obtained after mixing and refining be further improved, but also the effect of melt extrusion processing can be improved, so that the surface of the prepared sheet is smooth. Among them, polyethylene wax has a strong internal lubricating effect and a weak external lubricant effect, which can reduce the friction between the high-performance composite sheet materials, reduce the difficulty of mixing, and improve the mixing uniformity of the waste wind turbine blade material in the thermoplastic resin, thereby improving the mechanical properties of the high-performance composite sheet.

[0041] In one embodiment, the release agent includes one or more of sodium stearate, magnesium stearate and calcium stearate.

[0042] In one embodiment, the pigment includes red iron oxide and / or yellow iron oxide.

[0043] A second aspect of the present disclosure provides a method for preparing the high-performance composite board according to the first aspect, the method comprising: S1. Putting waste wind turbine blade materials and silane coupling agent dilution liquid into a high-speed mixer for premixing; the waste wind turbine blade materials include waste wind turbine blade powder and waste wind turbine blade degraded glass fiber; S2, putting the thermoplastic resin, compatibilizer, wood powder, filler, lubricant, release agent and pigment into the high-speed mixer and mixing with the mixed material in step S1 to obtain a composite board mixture; S3, allowing the composite plate mixture to enter a granulator for granulation treatment to obtain composite resin particles; S4, allowing the composite resin particles to enter a conical twin-screw extruder for extrusion molding to obtain a high-performance composite sheet; The material composition of the composite board mixture includes: relative to 160 parts by weight of the thermoplastic resin, the content of the waste wind turbine blade powder is 50-200 parts by weight, the content of the degraded glass fiber of the waste wind turbine blade is 5-40 parts by weight, the content of the silane coupling agent is 5-50 parts by weight, the content of the compatibilizer is 5-80 parts by weight, the content of the wood powder is 50-200 parts by weight, the content of the filler is 5-50 parts by weight, the content of the lubricant is 5-35 parts by weight, the content of the release agent is 5-35 parts by weight, and the content of the pigment is 1-10 parts by weight.

[0044] Through the above technical scheme, the present invention fully mixes the waste wind turbine blade powder, the degraded glass fiber of the waste wind turbine blade and the silane coupling agent, and then mixes and refines them with thermoplastic resin, compatibilizer, wood powder, filler, release agent and pigment to make high-performance composite board; on the one hand, it can reduce the manufacturing cost of high-performance composite board, and can also recycle and reuse the powder made of waste wind turbine blades and the recycled glass fiber obtained by chemical degradation method, so as to realize the resource utilization of retired wind turbine blades and effectively solve the problem of resource utilization of retired wind turbine blades; on the other hand, it can form a good synergistic effect between the various components, and can obtain a modified performance composite board with good mechanical properties such as tensile resistance, bending resistance and compression resistance.

[0045] In one implementation, step S1 includes: S11, cutting, crushing and sieving the waste wind turbine blades in sequence to obtain the waste wind turbine blade powder with a particle size of 40-200 mesh; S12, cutting, chemically degrading, washing, drying and segmenting the waste wind turbine blades in sequence to obtain the degraded glass fibers of the waste wind turbine blades with a length of 0.5-3 cm; S13, placing the waste wind turbine blade powder and the waste wind turbine blade degraded glass fiber into the high-speed mixer for stirring, and spraying the silane coupling agent dilution liquid into the mixer during the stirring process; S14, continue stirring the high-speed mixer at a rotation speed of 550-650 r / min for 10-30 min; S15, cooling the mixture obtained in step S14 to 20-30°C.

[0046] In one embodiment, the waste wind turbine blades are first cleaned before being cut, wherein the cleaning process is a conventional method in the art and is not specifically required in this application.

[0047] In one embodiment, the chemical degradation described in step S12 includes: placing the cut material obtained after cutting in an organic solvent containing an alkali, and reacting for 280 to 310 minutes at a temperature of 160 to 175° C. and a pressure of 0.9 to 1.1 MPa; wherein the alkali includes sodium hydroxide and / or magnesium hydroxide, and the organic solvent includes polyethylene glycol and / or polypropylene glycol.

[0048] In one embodiment, the washing in step S12 includes: filtering the chemically degraded reaction material to obtain glass fiber filaments, soaking the glass fiber filaments in a sizing agent for more than 1 minute, and then filtering to obtain the waste wind turbine blade degraded glass fiber. The sizing agent includes water.

[0049] In one embodiment, the drying described in step S12 is a conventional method in the art, and this application does not make any special requirements, as long as the wetting agent in the degraded glass fiber of the waste wind turbine blades can be removed.

[0050] In one embodiment, the silane coupling agent diluent in step S13 is a mixture of silane coupling agent and ethanol, wherein the ethanol is anhydrous ethanol.

[0051] In one embodiment, the mass concentration of the silane coupling agent in the silane coupling agent dilution solution is 30-60%.

[0052] In one embodiment, the stirring process conditions in step S13 include: the high-speed mixer rotates at a speed of 550-650 r / min for a time of 10-30 min.

[0053] In one embodiment, the mixing and stirring conditions in step S2 include: the high-speed mixer rotates at a speed of 550-650 r / min, preferably 600-620 r / min; and the mixing time is 30-60 min, preferably 40-50 min.

[0054] In one embodiment, the granulator described in step S3 is a conventional choice in the art and is not specifically required in this application.

[0055] In one embodiment, the conditions of the granulation treatment described in step S3 include: the temperature of the feeding section in the granulator is 160-210°C, the temperature of the plasticizing section in the granulator is 150-190°C, and the temperature of the extrusion section in the granulator is 140-180°C.

[0056] In a preferred embodiment, the conditions of the granulation treatment described in step S3 include: the temperature of the feeding section in the granulator is 190-200°C, the temperature of the plasticizing section in the granulator is 160-180°C, and the temperature of the extrusion section in the granulator is 150-170°C.

[0057] In one embodiment, the particle size of the composite resin particles described in step S3 can be flexibly adjusted according to actual production needs, which will not be described in detail here. In this embodiment, the composite sheet material mixture is made into particles with a suitable particle size, which can improve the effect of subsequent extrusion molding processing, thereby improving the mechanical properties of the high-performance composite sheet.

[0058] In one embodiment, the conical twin-screw extruder described in step S4 is a conventional choice in the art and is not specifically required in this application.

[0059] In one embodiment, the extrusion molding conditions described in step S4 include: the temperature of the feeding section in the conical twin-screw extruder is 170-220°C, the temperature of the plasticizing section in the conical twin-screw extruder is 150-200°C, and the temperature of the extrusion section in the conical twin-screw extruder is 140-180°C.

[0060] In a preferred embodiment, the extrusion molding conditions described in step S4 include: the temperature of the feeding section in the conical twin-screw extruder is 180-200°C, the temperature of the plasticizing section in the conical twin-screw extruder is 160-180°C, and the temperature of the extrusion section in the conical twin-screw extruder is 150-170°C.

[0061] In one embodiment, step S4 further includes placing the material at the outlet of the conical twin-screw extruder in a mold of a high-performance composite board, and obtaining the high-performance composite board after cooling to room temperature.

[0062] In one embodiment, the method for preparing the high-performance composite sheet comprises: S11, cutting, crushing and sieving the waste wind turbine blades in sequence to obtain the waste wind turbine blade powder with a particle size of 40-200 mesh; S12, cutting, chemically degrading, washing, drying and segmenting the waste wind turbine blades in sequence to obtain the degraded glass fibers of the waste wind turbine blades with a length of 0.5-3 cm; S13, placing the waste wind turbine blade powder and the waste wind turbine blade degraded glass fiber into the high-speed mixer for stirring, and spraying the silane coupling agent dilution liquid into the mixer during the stirring process; S14, continue stirring the high-speed mixer at a rotation speed of 550-650 r / min for 10-30 min; S15, cooling the mixture obtained in step S14 to 20-30° C.; S2, putting the thermoplastic resin, compatibilizer, wood powder, filler, lubricant, release agent and pigment into the high-speed mixer to mix with the mixed material in step S1, and stirring for 30-60 minutes in the high-speed mixer at a speed of 550-650 r / min to obtain a composite board mixture; The composition of the composite board mixture includes: relative to 160 parts by weight of the thermoplastic resin, the content of the waste wind turbine blade powder is 50-200 parts by weight, the content of the degraded glass fiber of the waste wind turbine blade is 5-40 parts by weight, the content of the silane coupling agent is 5-50 parts by weight, the content of the compatibilizer is 5-80 parts by weight, the content of the wood powder is 50-200 parts by weight, the content of the filler is 5-50 parts by weight, the content of the lubricant is 5-35 parts by weight, the content of the release agent is 5-35 parts by weight, and the content of the pigment is 1-10 parts by weight; S3, allowing the composite plate mixture to enter a granulator for granulation treatment to obtain composite resin particles; the granulation treatment conditions include: the temperature of the feeding section in the granulator is 160-210°C, the temperature of the plasticizing section in the granulator is 150-190°C, and the temperature of the extrusion section in the granulator is 140-180°C; S4. The composite resin particles are extruded into a conical twin-screw extruder to obtain a high-performance composite sheet. The extrusion molding conditions include: the temperature of the feeding section of the conical twin-screw extruder is 170-220°C, the temperature of the plasticizing section of the conical twin-screw extruder is 150-200°C, and the temperature of the extrusion section of the conical twin-screw extruder is 140-180°C.

[0063] The present disclosure is further described below by way of examples, but the present disclosure is not limited thereby. Unless otherwise specified, the compounds used in the following examples and comparative examples are all purchased pharmaceutical reagents.

[0064] Example 1 The method for preparing the high-performance composite sheet comprises: S11, cutting, crushing and sieving the waste wind turbine blades in sequence to obtain waste wind turbine blade powder with a particle size of 40 mesh; S12, cutting, chemically degrading, washing, drying and cutting the waste wind turbine blades in sequence to obtain degraded glass fibers of the waste wind turbine blades with a length of 0.5 cm; S13, 50 parts by weight of waste wind turbine blade powder and 5 parts by weight of degraded glass fiber of waste wind turbine blades are put into the high-speed mixer for stirring, and 5 parts by weight of silane coupling agent KH550 diluted solution (30% alcohol solution) are sprayed into the mixer during the stirring process; S14, the high-speed mixer is allowed to continue stirring for 20 min at a rotation speed of 600 r / min; S15, cooling the mixture obtained in step S14 to 25° C.; S2, 160 parts by weight of polypropylene, 5 parts by weight of maleic anhydride grafted polypropylene, 200 parts by weight of 60-mesh poplar powder, 5 parts by weight of calcium carbonate, 5 parts by weight of polyethylene wax, 5 parts by weight of sodium stearate and 1 part by weight of red iron oxide are put into the high-speed mixer and mixed with the mixture obtained in step S15, and stirred for 30 minutes in the high-speed mixer at a speed of 600 r / min to obtain a composite plate mixture; S3, allowing the composite plate mixture to enter a granulator for granulation treatment to obtain composite resin particles; the granulation treatment conditions include: the temperature of the feeding section in the granulator is 160° C., the temperature of the plasticizing section in the granulator is 150° C., and the temperature of the extrusion section in the granulator is 140° C.; S4. The composite resin particles are extruded into a conical twin-screw extruder to obtain a high-performance composite plate a having a size of 2m×12mm×20mm; the extrusion molding conditions include: the temperature of the feeding section in the conical twin-screw extruder is 170°C, the temperature of the plasticizing section in the conical twin-screw extruder is 150°C, and the temperature of the extrusion section in the conical twin-screw extruder is 140°C.

[0065] Example 2 The method for preparing the high-performance composite sheet is the same as that in Example 1, except that: 200 parts by weight of waste wind turbine blade powder (200 mesh) and 40 parts by weight of waste wind turbine blade degraded glass fiber (3 cm) are placed in a high-speed mixer, slowly stirred, and 50 parts by weight of silane coupling agent KH560 dilution (60% alcohol solution) are sprayed, and then the speed is increased to 600r / min and continued to stir for 20min before cooling to room temperature. 160 parts by weight of polyethylene, 60 parts by weight of maleic anhydride grafted polyethylene, 50 parts by weight of 100-mesh poplar powder, 50 parts by weight of talcum powder, 35 parts by weight of polyethylene wax, 35 parts by weight of calcium stearate, and 10 parts by weight of iron oxide yellow are added, the speed is increased to 600r / min, and stirred for 60min to obtain a composite sheet mixture. The composite sheet mixture is granulated using a granulator to obtain composite resin particles, and the granulation temperature is set to: 210°C for the feeding section, 190°C for the plasticizing section, and 180°C for the extrusion section. The composite resin particles were placed into the hopper of a conical twin-screw extruder. The operating temperature of the extruder was set to: 220°C for the feeding section, 200°C for the plasticizing section, and 180°C for the extrusion section. The high-performance composite sheet b was obtained by slow extrusion.

[0066] Example 3 The method for preparing the high-performance composite sheet is the same as that in Example 1, except that: 150 parts by weight of waste wind turbine blade powder (100 mesh) and 20 parts by weight of degraded glass fiber of waste wind turbine blade (1 cm) are placed in a high-speed mixer, slowly stirred, and 20 parts by weight of silane coupling agent KH550 dilution (50% alcohol solution) are sprayed, and then the speed is increased to 600r / min and continued to stir for 20min before cooling to room temperature. 160 parts by weight of polyethylene, 30 parts by weight of maleic anhydride grafted polyethylene, 150 parts by weight of 60-mesh eucalyptus powder, 30 parts by weight of talcum powder, 20 parts by weight of polyethylene wax, 20 parts by weight of magnesium stearate, and 5 parts by weight of iron oxide yellow are added, the speed is increased to 600r / min, and stirred for 50min to obtain a composite sheet mixture. The composite sheet mixture is granulated using a granulator to obtain composite resin particles, and the granulation temperature is set to: 190°C for the feeding section, 175°C for the plasticizing section, and 170°C for the extrusion section. The composite resin particles were placed into the hopper of a conical twin-screw extruder. The operating temperature of the extruder was set to: 190°C for the feeding section, 170°C for the plasticizing section, and 165°C for the extrusion section. The high-performance composite sheet c was obtained by slow extrusion.

[0067] Example 4 The method for preparing the high-performance composite sheet is the same as that in Example 1, except that: 100 parts by weight of waste wind turbine blade powder (100 mesh) and 20 parts by weight of degraded glass fiber of waste wind turbine blade (2 cm) are placed in a high-speed mixer, slowly stirred, and 20 parts by weight of silane coupling agent KH560 dilution (50% alcohol solution) are sprayed, and then the speed is increased to 600r / min and continued to stir for 20min before cooling to room temperature. 160 parts by weight of polypropylene, 30 parts by weight of maleic anhydride grafted polypropylene, 200 parts by weight of 60-mesh poplar powder, 30 parts by weight of calcium carbonate, 20 parts by weight of polyethylene wax, 20 parts by weight of calcium stearate, and 5 parts by weight of red iron oxide are added, the speed is increased to 600r / min, and the composite sheet mixture is obtained after stirring for 30min. The composite sheet mixture is granulated using a granulator to obtain composite resin particles, and the granulation temperature is set to: 200°C for the feeding section, 180°C for the plasticizing section, and 170°C for the extrusion section. The composite resin particles were placed into the hopper of a conical twin-screw extruder. The operating temperature of the extruder was set to: 200°C for the feeding section, 180°C for the plasticizing section, and 170°C for the extrusion section. The high-performance composite sheet d was obtained by slow extrusion.

[0068] Example 5 The method for preparing the high-performance composite sheet is the same as that in Example 1, except that: 160 parts by weight of waste wind turbine blade powder (80 mesh) and 20 parts by weight of waste wind turbine blade degraded glass fiber (1 cm) are placed in a high-speed mixer, slowly stirred, and 40 parts by weight of silane coupling agent KH550 dilution (60% alcohol solution) are sprayed, and then the speed is increased to 600r / min and continued to stir for 20min before cooling to room temperature. 160 parts by weight of polyethylene, 60 parts by weight of maleic anhydride grafted polyethylene, 160 parts by weight of 80-mesh poplar powder, 30 parts by weight of calcium carbonate, 20 parts by weight of polyethylene wax, 20 parts by weight of calcium stearate, and 5 parts by weight of red iron oxide are added, the speed is increased to 600r / min, and the composite sheet mixture is obtained after stirring for 50min. The composite sheet mixture is granulated using a granulator to obtain composite resin particles, and the granulation temperature is set to: 200°C for the feeding section, 180°C for the plasticizing section, and 170°C for the extrusion section. The composite resin particles were placed into the hopper of a conical twin-screw extruder. The operating temperature of the extruder was set to: 190°C for the feeding section, 175°C for the plasticizing section, and 160°C for the extrusion section. The high-performance composite sheet e was obtained by slow extrusion.

[0069] Example 6 The method for preparing the high-performance composite board is the same as that in Example 5, except that the particle size of the waste wind turbine blade powder is 300 mesh, and a high-performance composite board f is obtained.

[0070] Example 7 The method for preparing the high-performance composite board is the same as that in Example 5, except that the length of the degraded glass fiber from waste wind turbine blades is 4 cm, and the high-performance composite board g is obtained.

[0071] Example 8 The method for preparing the high-performance composite board is the same as that in Example 5, except that the mass concentration of the silane coupling agent in the silane coupling agent dilution solution is 70%, and a high-performance composite board h is obtained. Comparative Example 1 The method for preparing the high-performance composite board is the same as that in Example 5, except that: no degraded glass fiber from waste wind turbine blades is used to obtain the high-performance composite board i.

[0072] Comparative Example 2 The method for preparing the high-performance composite board is the same as that in Example 5, except that waste wind turbine blade powder, degraded glass fiber of waste wind turbine blades, silane coupling agent KH550 dilution, polyethylene, maleic anhydride grafted polyethylene, 80 mesh poplar powder, calcium carbonate, polyethylene wax, calcium stearate and red iron oxide are added together into a high-speed mixer, and the composite board is mixed to obtain a high-performance composite board j.

[0073] Comparative Example 3 The method for preparing the high-performance composite board is the same as that in Example 5, except that: relative to 160 parts by weight of the thermoplastic resin, the content of the waste wind turbine blade powder is 300 parts by weight, the content of the degraded glass fiber of the waste wind turbine blade is 45 parts by weight, the content of the silane coupling agent is 55 parts by weight, the content of the compatibilizer is 60 parts by weight, the content of the wood powder is 300 parts by weight, the content of the filler is 55 parts by weight, the content of the lubricant is 50 parts by weight, the content of the release agent is 50 parts by weight, and the content of the pigment is 5 parts by weight, to obtain a high-performance composite board k.

[0074] Test Case The high-performance composite panels a~k prepared in Examples 1~8 and Comparative Examples 1~3, as well as the blade regeneration profile samples (provided by Warner Environmental Protection) and the commercially available wood-plastic panels (Shi Teng plastic wood) were tested for tensile strength, bending strength and compressive strength by a universal testing machine. The universal testing machine is a WDW-30 universal testing machine produced by Thornton Instruments. The tensile strength test method refers to GB / T 1040.2-2006, the bending strength test method refers to GB / T 9341-2008, and the compressive strength test method refers to GB / T 1041-2008. The test results are shown in Table 1.

[0075] Table 1 Performance parameters of high performance composite panels

[0076] As described in Table 1, according to the comparison of the data between Examples 1 to 8 and Comparative Examples 1 to 5, the coupling effect of waste wind turbine blade powder and waste wind turbine blade degraded glass fiber with thermoplastic resin is good, and under the synergistic effect of materials such as compatibilizers, wood powder, fillers and lubricants, the mixing and stirring effect can be improved, and the waste wind turbine blade powder and waste wind turbine blade degraded glass fiber can be evenly dispersed in the high-performance composite board, which can improve the tensile, bending and compression physical properties of the composite board. According to the comparison of the data in Example 5 and Example 6, when the particle size of the waste wind turbine blade powder is 40-200 mesh, the tensile, bending and compression physical properties of the composite board can be improved. According to the comparison of the data in Example 5 and Example 7, when the length of the waste wind turbine blade degraded glass fiber is 0.5-3cm, the tensile, bending and compression physical properties of the composite board can be improved. According to the comparison of the data in Example 5 and Example 8, when the mass concentration of the silane coupling agent in the silane coupling agent dilution solution is 30-60%, the tensile, bending and compression physical properties of the composite board can be improved.

[0077] The preferred embodiments of the present disclosure are described in detail above; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.

[0078] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.

[0079] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.

Claims

1. A high-performance composite board made from waste wind turbine blades, characterized in that: The materials for preparing the high-performance composite board include waste wind turbine blade materials, silane coupling agents, thermoplastic resins, compatibilizers, wood powder, fillers, lubricants, release agents and pigments; wherein the waste wind turbine blade materials include waste wind turbine blade powder and waste wind turbine blade degraded glass fibers; Relative to 160 parts by weight of the thermoplastic resin, the content of the waste wind turbine blade powder is 50-200 parts by weight, the content of the degraded glass fiber of the waste wind turbine blade is 5-40 parts by weight, the content of the silane coupling agent is 5-50 parts by weight, the content of the compatibilizer is 5-80 parts by weight, the content of the wood powder is 50-200 parts by weight, the content of the filler is 5-50 parts by weight, the content of the lubricant is 5-35 parts by weight, the content of the release agent is 5-35 parts by weight, and the content of the pigment is 1-10 parts by weight.

2. The high performance composite sheet according to claim 1, characterized in that: The silane coupling agent includes KH550 and / or KH560.

3. The high performance composite sheet according to claim 1, characterized in that: The particle size of the waste wind turbine blade powder is 40-200 mesh; The length of the degraded glass fiber of the waste wind turbine blades is 0.5-3 cm.

4. The high performance composite sheet according to claim 1, characterized in that: Relative to 160 parts by weight of the thermoplastic resin, the content of the waste wind turbine blade powder is 100-180 parts by weight, the content of the degraded glass fiber of the waste wind turbine blade is 10-30 parts by weight, the content of the silane coupling agent is 10-45 parts by weight, the content of the compatibilizer is 10-70 parts by weight, the content of the wood powder is 100-180 parts by weight, the content of the filler is 10-40 parts by weight, the content of the lubricant is 10-30 parts by weight, the content of the release agent is 10-30 parts by weight, and the content of the pigment is 2-8 parts by weight.

5. The high performance composite sheet according to claim 1, characterized in that: The thermoplastic resin includes polypropylene and / or polyethylene; The wood powder includes poplar wood powder and / or eucalyptus wood powder; the particle size of the wood powder is 50-150 mesh; The compatibilizer includes maleic anhydride grafted polypropylene and / or maleic anhydride grafted polyethylene; The filler includes calcium carbonate and / or talc; The lubricant includes polyethylene wax; The release agent includes one or more of sodium stearate, magnesium stearate and calcium stearate; The pigment includes red iron oxide and / or yellow iron oxide.

6. A method for preparing the high-performance composite sheet according to any one of claims 1 to 5, characterized in that: The method includes: S1. Putting waste wind turbine blade materials and silane coupling agent dilution liquid into a high-speed mixer for premixing; the waste wind turbine blade materials include waste wind turbine blade powder and waste wind turbine blade degraded glass fiber; S2, putting the thermoplastic resin, compatibilizer, wood powder, filler, lubricant, release agent and pigment into the high-speed mixer and mixing with the mixed material in step S1 to obtain a composite board mixture; S3, allowing the composite plate mixture to enter a granulator for granulation treatment to obtain composite resin particles; S4, allowing the composite resin particles to enter a conical twin-screw extruder for extrusion molding to obtain a high-performance composite sheet; The material composition of the composite board mixture includes: relative to 160 parts by weight of the thermoplastic resin, the content of the waste wind turbine blade powder is 50-200 parts by weight, the content of the degraded glass fiber of the waste wind turbine blade is 5-40 parts by weight, the content of the silane coupling agent is 5-50 parts by weight, the content of the compatibilizer is 5-80 parts by weight, the content of the wood powder is 50-200 parts by weight, the content of the filler is 5-50 parts by weight, the content of the lubricant is 5-35 parts by weight, the content of the release agent is 5-35 parts by weight, and the content of the pigment is 1-10 parts by weight.

7. The method according to claim 6, characterized in that Step S1 includes: S11, cutting, crushing and sieving the waste wind turbine blades in sequence to obtain the waste wind turbine blade powder with a particle size of 40-200 mesh; S12, cutting, chemically degrading, washing, drying and segmenting the waste wind turbine blades in sequence to obtain the degraded glass fibers of the waste wind turbine blades with a length of 0.5-3 cm; S13, placing the waste wind turbine blade powder and the waste wind turbine blade degraded glass fiber into the high-speed mixer for stirring, and spraying the silane coupling agent dilution liquid into the mixer during the stirring process; S14, continue stirring the high-speed mixer at a rotation speed of 550-650 r / min for 10-30 min; S15, cooling the mixture obtained in step S14 to 20-30°C.

8. The method according to claim 7, characterized in that The mass concentration of the silane coupling agent in the silane coupling agent dilution solution is 30-60%.

9. The method according to claim 6, characterized in that Step S3 also includes that the conditions of the granulation treatment include: the temperature of the feeding section in the granulator is 160-210°C, the temperature of the plasticizing section in the granulator is 150-190°C, and the temperature of the extrusion section in the granulator is 140-180°C.

10. The method according to claim 6, characterized in that Step S4 also includes that the extrusion molding conditions include: the temperature of the feeding section in the conical twin-screw extruder is 170-220°C, the temperature of the plasticizing section in the conical twin-screw extruder is 150-200°C, and the temperature of the extrusion section in the conical twin-screw extruder is 140-180°C.

Citation Information

Patent Citations

  • Method for recovering waste thermosetting resin and composite materials thereof through solvents

    CN102617885A

  • Wood plastic board and preparation method thereof

    CN110746684A

  • Method for resourceful treatment of waste wind power blades

    CN116274253A

  • Glass-plastic tray and preparation method thereof

    CN116694098A

  • Method for producing reinforced thermoplastic composite material by utilizing wind power blade

    CN117445452A

Cited By

  • Composite template and preparation method thereof

    CN120422439A

  • Additive obtained by crushing and modifying wind power blade glass fibers and concrete using additive

    CN120664808A

  • An additive obtained by modifying glass fiber in wind turbine blades and concrete using the additive.

    CN120664808B

  • Composite board based on retired wind power blade and preparation method of composite board

    CN121343384A

  • Solvent-catalyst system and method for degrading epoxy resin material of retired wind turbine blade

    CN121895627A